(untitled) (Annals of Medical Research, 2024)
Aim: The use of online learning, which has spread rapidly worldwide in recent years, has increased considerably with the COVID-19 pandemic. The study aimed to evaluate the online learning experience of children attending primary school 1st grade and the relationship between online learning, related factors, and emotional/behavioral problems. Materials and Methods: This study was carried out with 378 mothers who have a child attending primary school 1st grade. Demographic data were assessed with the Sociodemographic Data Form, which included information about the online learning process and school, and the parent-rated Strengths and Difficulties Questionnaire (SDQ) to assess emotional/behavioral problems. Results: 50.5% of the mothers reported that their children experienced emotional/behavioral problems, while 45.3% reported that online learning exacerbated their children’s emotional/behavioral problems. SDQ emotional problems score was significantly higher in girls, while SDQ vonduct problems and Hyperactivity/inattention subscores, and SDQ total scores were significantly higher in boys. The SDQ peer problems subscore and SDQ total scores of illiterates were significantly higher than those of literates. There was a significant negative correlation between the extracurricular screen time and all SDQ scores except the prosocial behavior subscore. The SDQ conduct problems and peer problems subscores and SDQ total scores of children with regular activities/hobbies were significantly lower than the others, while the SDQ prosocial behavior score was significantly higher. Conclusion: Our study findings showed that online learning negatively affected almost half of the children in terms of emotional/behavioral problems for different reasons, gender can lead to differences in emotional/behavioral problems in early childhood, illiterate children and children with increased extracurricular screen time may be more at risk in terms of emotional/behavioral problems and regular activities/hobbies may contribute positively to the process.